Analisis Yuridis terhadap Implementasi Sistem Peradilan Pidana Anak di Indonesia - Febby Widiaryani (Jurnal Hukum dan Sosial Politik, 2026)
The Juvenile Criminal Justice System (SPPA) in Indonesia is a manifestation of special protection for children in conflict with the law, prioritizing the principles of restorative justice and diversion. This study aims to analyze the implementation of the SPPA based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and to identify the legal challenges that arise in its practice. The research method used is normative legal with a legislative and conceptual approach. The results of the study show that although the regulations mandate diversion efforts as a top priority in resolving juvenile cases, there are still obstacles in its implementation, both in terms of the readiness of law enforcement officials, limited supporting facilities, and the perception of the community, which still tends to expect a retributive (punitive) approach. In addition, the protection of children's rights during the judicial process is often not optimally fulfilled. This analysis concludes that strengthening inter-agency coordination and increasing law enforcement officials' understanding of restorative justice are key to the effectiveness of this system. Further regulatory harmonization and strengthening the role of the Correctional Center in overseeing the diversion process are needed to ensure that the best interests of the child remain the top priority at every stage of the judicial process